DET FREMMEDE HJEM: Bosniske flygtninges illusioner om hjemlandet - Stefansson, Anders Holm (Tidsskriftet Antropologi, 2000)
This article explores a range of illusions about refugee return, both from the perspective of political institutions and refugees themselves. The political repatriation discourse in Western European host countries is based upon illusory conceptions of people’s rootedness in specific territories and of return as an unproblematic re-establishment of the preflight conditions. Whereas refugee diasporas widely share this nostalgic celebration of the “return to the past”, for Bosnian refugees in Denmark the idealization of their homeland and “the myth of return”, rather than leading to the actual return to the country of origin, serve as a source of meaning, hope for normality, and community in exile. For the refugees who, voluntarily or involuntarily, do return to Bosnia-Hercegovina “home-coming” is an experience of disillusionment due to various war-related transformations of the Bosnian society, difficult socio-economic conditions found upon return, and discrimination and resentment from the remaining population. The returnees feel like strangers in their own country, and this in turn gives rise to longing for emigration and romanticized images of their past refugee life abroad.